Sustainable Cities for the Third Millennium: The Odyssey of Urban Excellence The Odyssey of Urban Excellence - Mega, Voula P. (Springer New York : Imprint: Springer, 2010)
Cities are propellers of sustainable growth, theatres of values, schools of skills and abilities, beacons of culture and temples of citizen duties and rights. Aristotle called them built politics , places which have the noble aim to offer citizens a fulfilling and worthy life. Cities have always been beehives of cross-fertilised creativity, the only places where people and resources congregate at a point beyond which synergetic effects become more important than the simply additive ones. The book offers a 360ˌview of the challenges facing cities at the dawn of the millennium in terms of growth, governance, environmental well-being, social inclusion, science, culture and the arts, urban renaissance and planning. One year after the crisis that started in 2008, the book presents responses to overcome the crisis of values and engage in a sustainability path from European and world cities. It tries to distil useful messages for all cities wishing to adopt bolder and better policy initiatives. Each chapter focuses on an essential dimension of the sustainable city and presents, in a nutshell, visions and actions of cities that herald meaningful far-reaching change.